Hubungan Duduk Lama Dan Statis Dalam Membatik Terhadap Fleksibilitas Lumbal Di Danar Hadi Surakarta - Dewi, Fitri Kusuma; , Dwi Rosella K, S.St FT., M.Fis; , Agus Widodo, S.Fis, M.Kes (2016)
Background: Flexibility is defined as the ability of muscles to contract and return to its initial state without any pain or any obstacles. Flexibility is defined as the ability to perform a certain movement in the joint or joints in a combination of a functional group. Objective: To determine the relationship of prolonged sitting and static in batik to the flexibility of lumbar. Subjects: A total of 20 respondents who work with the old and static sitting Danar Hadi in Surakarta aged 40-54 years. Research Methodology: Hypothesis test used in this study is the correlation parametric test because of the type of data in the study is numerical data, therefore the data normality test used is the Shapiro-Wilk. Test used was Pearson, having already qualified namely normal data distribution. Results: Based on Pearson Test test obtained ap value of 0.001 so as it can be there's relation long sitting and statis of lumbal flexibility Danar Hadi in Suarakarta.